Influence of retrobulbar neuritis and papillitis on echographically measured optic nerve diameter - Stefanović Ivan B.; Jovanović Miloš; Dačić-Krnjaja Bojana; Veselinović Dragan; Jovanović Predrag (Vojnosanitetski Pregled)
Background/Aim. Retrobulbar (optic) neuritis is inflammation of the optic nerve that may cause a complete or partial loss of vision. This inflammation can affect a part of the nerve within the eyeball (neuropapillitis) or a part of the nerve behind the eyeball (retrobulbar neuritis). The aim of this study was to establish whether there is a correlation between the diameter of a retrobulbar part of the optic nerve and either visual acuity, prominence of the optic disk (papillitis), or nature of the neuritis (papillitis or retrobulbar). Methods. We tested 23 patients with retrobulbar neuritis and papillitis. In addition to a complete ophthalmologic examination, the diameter of retrobulbar region of the optic nerve was measured by the B-scan method. Following this, the 30-degree test was carried out. Results. We found an increased thickness of the retrobulbar region in 22 patients and different responses to the 30-degree test, as well as a statistically significant negative correlation between the thickness of retrobulbar part of the optic nerve and visual acuity. Conclusion. The retrobulbar part of the optic nerve is thicker in 94% of the patients with retrobulbar neuritis and in all the patients with papillitis. There is a correlation between the reduction of visual acuity and thickening of a retrobulbar part.